CULTURE TRANSFORMATION: LESSONS FROM BANK MANDIRI AND BANK BRI - Mahmuddin Yasin (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2014)
This research aims at exploring organizational culture in state owned enterprises; BankMandiri and Bank BRI, and its contribution to financial performance, before and afterrestructuring/initial public offering (IPO). The research used qualitative approach with casestudy method that used coupled with exploratory and descriptive design, supported bysuccessive approximation of technical data analysis. Eight propositions were raised from thefindings regarding: (1) integration human resources planning with corporate plan, (2) skilldevelopment accommodating individual, organizational and business needs, (3) effectivestrategy aligned with appropriate system and proper business orientation, (4) suitableorganizational structure with internal and external business environment, (5) systemdevelopment oriented to customer satisfaction, (6) proper style of leadership that affectsorganizational culture and financial performance, (7) implementation of organizational culturein increasing corporate performance, and (8) consistency in socializing and implementingcorporate culture.Keywords: state owned enterprises, organizational culture, restructuring/IPO, successiveapproximation, proposition.